Georgia Country Economic Update, February 2018 : Making the Recovery Sustainable - World Bank Group (World Bank, Washington, DC, 2018)
The country benefited from the improved external demand in 2017. Global growth is estimated to have picked up in 2017 to 3.0 percent from 2.4 percent in 2016, reflecting gradual recovery in the euro area, China, emerging Europe, and Russia as commodity prices and financial markets continued to stabilize. With growth outcomes in 2017 generally stronger than expected, Georgia's annual growth estimate was revised to 4.2 percent, compared to an earlier projection of 3.5 percent. Higher growth is likely to have improved population incomes, following adverse social outcomes in 2016 (figure 1). In 2016, poverty indicators deteriorated to 25.6 percent from 25.3 percent in 2015 (at 3.2 US dollars a day in 2011 PPP terms).